Overcoming Newcastle disease in rural family poultry: evaluating vaccine efficacy and field challenges in Burkina Faso - Ouedraogo, A.; Dione, Michel M.; Ouoba, L.B.; Ilboudo, Guy S.; Ouedraogo, Brice; Mungadi, H.U.; Alders, R. (Centre de Coopération Internationale en Recherche Agronomique pour le Développement, 2025)
Background: Newcastle disease (ND) is one of the most common diseases in poultry production, causing high mortality rates and significant economic losses. Controlling this enzootic disease in rural poultry flocks has been challenging in many low- and middle-income countries (LMICs).